1992
DOI: 10.1086/229941
|View full text |Cite
|
Sign up to set email alerts
|

Successful Aging: A Life-Course Perspective on Women's Multiple Roles and Health

Abstract: Successful Aging such difficulties quite early in life. Most important, many people deal well with particular afflictions, while others with the same difficulties become functionally impaired. While there are diverse definitions of health, we prefer to consider health as a multidimensional continuum, rather than a dichotomy, and in terms of functional abilities and the absence of chronic disease in addition to subjective assessments of one's fitness (Antonovsky 1987). One promising corollary, and possible prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
269
1
6

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(284 citation statements)
references
References 30 publications
8
269
1
6
Order By: Relevance
“…Many social gerontologists have labeled the period of old age as that of role loss, with the elderly living alone having few family roles that are formed through interaction with family members. Previous studies have found that having various social roles, including family roles, increase subjective well-being (Adelman, 1994;Greenfield & Marks, 2004;Moen, Dempster-McClain, & Williams, 1992;Rushing, Litter, & Burton, 1992;Sugihara, Sugisawa, Shibata, & Harada, 2008). We predict that elderly people living alone will have lower subjective well-being than elderly people living with their families.…”
Section: Problemmentioning
confidence: 66%
“…Many social gerontologists have labeled the period of old age as that of role loss, with the elderly living alone having few family roles that are formed through interaction with family members. Previous studies have found that having various social roles, including family roles, increase subjective well-being (Adelman, 1994;Greenfield & Marks, 2004;Moen, Dempster-McClain, & Williams, 1992;Rushing, Litter, & Burton, 1992;Sugihara, Sugisawa, Shibata, & Harada, 2008). We predict that elderly people living alone will have lower subjective well-being than elderly people living with their families.…”
Section: Problemmentioning
confidence: 66%
“…2,[4][5][6] Volunteering appears to confer substantial benefits to the older adults themselves. [7][8][9][10][11][12][13][14][15] The benefits range from the opportunity to be productive and to be socially engaged and generative, 16 to known health benefits of regular, structured activities and remaining physically and cognitively active. These individual benefits, if organized on a larger scale, could have substantial public health benefits if senior volunteer roles were carefully designed to double as a social model for health promotion for an aging society.…”
Section: Introductionmentioning
confidence: 99%
“…Moen et al, 1992) [2]. But are healthy people more likely to possess more roles, or are they likely to be engaged in more roles because they are healthier (Wethington et al, 2000) [1]?…”
Section: Discussionmentioning
confidence: 99%
“…Expanding on the work of Elder (1985) [3] Moen et al, (1992) [2] submits that there are three life course themes: timing, process, and context. As mentioned, Verbrugge (1983) [25] found that women who are employed have better health outcomes.…”
mentioning
confidence: 99%